MENGANALISIS DAN MENGEVALUASI BERBAGAI TEORI DAN KOMPONEN CHANGE MANAJEMEN UNTUK MEMBERIKAN ALTERNATIF SOLUSI PERMASALAHAN RIIL PADA PENDIDIKAN TEKNOLOGI DAN KEJURUAN - Arni Sulistyowati; Fransiska Dwi Yunitasari; Fajariati Herina Putri; Joko; Ismet Basuki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Vocational education plays a strategic role in preparing a competent workforce in an ever-evolving industrial era. However, challenges such as rapid technological advancements, gaps between curricula and industry needs, and educator readiness remain major obstacles. This study aims to analyze and evaluate various theories and practices of Change Management to provide solutions for vocational education. The research method used is a literature review focusing on the ADKAR Model, which includes awareness, desire, knowledge, ability, and reinforcement of change. The findings indicate that effective implementation of Change Management can enhance graduates' readiness for the workforce, whether as employees, entrepreneurs, or students pursuing higher education. Key strategies that need to be implemented include industry collaboration, continuous training for educators, modernization of learning facilities, and increased motivation and engagement among students.